The analysis of geometrically nonlinear elastic-plastic space frames - Karkauskas, Romanas; Popov, Michail (Journal of Civil Engineering and Management, 2011)
The establishment of the real stress-strain state of the structure is one of the most important problems for designing and undertaking the reconstruction of building constructions as well as making calculations for the purpose of optimizing cross-sections of various structural elements. This task can be achieved by analysing the structure as a geometrically nonlinear system (refusing an assumption of small displacements) and taking into consideration plastic deformations. Modern computer technologies and mathematical tools enable us to perform strength analysis of space structures and to increase the accuracy of stress-strain state analysis. The present paper develops a technique for constructing a finite element tangent matrix for the nonlinear analysis of the space frame structure aimed at determining plastic deformations. The mathematical models of the problems based on static and kinematic formulations using the dual theory of mathematical programming were created for analysis. Strength conditions presented in construction codes and specifications AISCLRFD and suggested by other researchers (e.g. Orbison’s strength conditions) are used in the formulations of the analysed problems. The mathematical models of the considered problems are tested by calculating a two-storied space frame. The results of the performed analysis are compared with data obtained within the studies conducted by other researchers. Tampriai plastinių geometriškai netiesinių erdvinių rėmų analizė Santrauka. Projektuojant ar rekonstruojant konstrukcijas, atliekant jos elementų skerspjūvių optimizavimo skaičiavimus, vienas iš svarbiausių uždavinių – konstrukcijos tikrojo įtempto deformuoto būvio (ĮDB) nustatymas. Tai galima pasiekti atliekant konstrukcijos kaip geometriškai netiesinės sistemos (atsisakant mažų poslinkių prielaidos) analizę, įvertinant plastines deformacijas. Taikant šiuolaikines kompiuterines technologijas ir matematinį aparatą, tapo įmanoma vykdyti erdvinės konstrukcijos stiprumo analizę ir padidinti konstrukcijos ĮDB analizės tikslumą. Tuo tikslu šiame darbe toliau plėtojama tangentinės standumo matricos sudarymo metodika erdvinės rėminės konstrukcijos netiesinei analizei, įvertinant plastines deformacijas. Naudojant matematinio programavimo dualumo teoriją sudaryti analizės statinės ir kinematinės formuluočių uždavinių matematiniai modeliai. Naudojamos AISC-LRFD normatyviniuose dokumentuose pateiktos ir kitų autorių (pavyzdžiui, Orbison) pasiūlytos stiprumo sąlygos. Suformuluoti analizės uždavinių matematiniai modeliai buvo aprobuoti skaičiuojant dviejų aukštų erdvinį rėmą. Gauti analizės rezultatai palyginti su eksperimentiniais ir kitų autorių analitiniais rezultatais. Reikšminiai žodžiai: tampriai plastinė erdvinė konstrukcija, geometrinis netiesiškumas, tangentinė standumo matrica, antrosios eilės analizė, MatLAB.